Analisis Sikap dan Perilaku Konsumen terhadap Minuman Kopral(kopi pakai gula aren) di Coffe Shop Gading Cempaka Kota Bengkulu - Muhammad Imam Zuhdi; Herri Fariadi; Ana Nurmalia; Ririn Afriani (Rashid : Journal of Economic, 2025)
The purpose of this study was to determine consumer attitudes towards Kopral Coffee Drink (Coffee with Gula Aren) and to determine consumer behavior towards Kopral Coffee Drink (Coffee with Gula Aren) at Coffe Shop Gading Cempaka, Bengkulu City. The research method used is quantitative and qualitative methods with the Fishbein model to determine consumer attitudes towards all product attributes including: taste, price, aroma, color, packaging and location. The results showed that consumer attitudes towards Kopral Coffee at Gading Cempaka Coffee Shop, Bengkulu City were positive with a total attitude value of 7.68, which means that the value of consumer attitudes is at a positive value for each attribute